Untold narratives and perspectives a production of documentary film series of women and drug dependence - Moreno, Michelle Anne N. (2018)
In the past, women were not included in most drug-related researches (NIDA, 2015). In an effort to understand women?s involvement in drugs and to add to the existing body of research on this matter, this research entitled Untold Narratives and Perspectives: a production of documentary film series of women and drug dependence, focused on narratives of women from drug initiation to progression to drug dependence. Guided by Nancy Hartsock?s feminist standpoint theory, the researcher highlighted the marginalized group of drug dependents ? specifically women drug dependents residing at the Davao City Treatment and Rehabilitation Center for Drug Dependents. The researcher selected three participants with the most gripping and never-before-heard stories and used these to produce the documentary film series. These three webisodes, namely (1) ?Carrier?, (2) ?Choice?, and (3) ?Escape, were composed of clips from the audio and videotaped key informant interviews. In order to secure the privacy and confidentiality of their identities., the researcher only shot the eyes, mouth, and hands of the participants as they spoke. Also, the researcher made and utilized a Facebook page entitled Untold Stories of Drug Dependence where she posted the three webisodes.